Influence of fruit traits on oviposition preference of the olive fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae), on three Portuguese olive varieties (Cobrançosa, Madural and Verdeal Transmontana) - Gonçalves, Fátima M. (2016)
The olive fly, Bactrocera oleae (Rossi), is the major pest of olives in Mediterranean countries. Previous studies have stated that different olive tree varieties are not infested at the same time. Thus, in this work, the objective was to investigate several fruit physical and chemical parameters that could influence the B. oleae infestation progress in three olive varieties with different susceptibility degrees (Cobranc¸ osa, Madural and Verdeal Transmontana). Concerning physical parameters, the influence of maturity index, weight, volume and puncture resistance was studied, while in chemical parameters moisture, oil content and fatty acids composition were determined. Physical factors do not seem to be a determinant factor for selection of varieties. However, such factors could be important within the variety since the oviposition was correlated with some of them, being positively correlated with maturity index and negatively correlated with hardness in all varieties, with the stronger correlations observed in Cobranc¸ osa. For Madural and Cobranc¸ osa, a positive correlation was also established between oviposition and weight and volume. Concerning the chemical parameters, based on the principal component analysis, it was possible to separate the three varieties, which allows for concluding that they are chemically distinct. There are reasons to believe that some of these chemical parameters, namely the fatty acids composition, may influence the olive fly in the selection of the olive variety for oviposition.